Life stage-specific trends in educational inequalities in health-related quality of life and self-rated health between 2002 and 2016 in Germany: findings from the German Socio-Economic Panel Study (GSOEP). Issue 3 (4th March 2021) - Sperlich, Stefanie; Klar, Marie Kristin; Safieddine, Batoul; Tetzlaff, Fabian; Tetzlaff, Juliane; Geyer, Siegfried
Abstract : Objectives: While evidence suggests persisting health inequalities, research on whether these trends may vary according to different stages of life has rarely been considered. Against this backdrop, we analysed life stage-specific trends in educational inequalities in health-related quality of life (HRQOL) and poor self-rated health (SRH) for individuals in 'later working life' (50–64 years), 'young seniors' (65–79 years) and persons of 'old age' (80+ years). Methods: We used survey data from the German Socio-Economic Panel Study comprising the period from 2002 to 2016. The sample consists of 26 074 respondents (160 888 person-years) aged 50 years and older. Health was assessed using the mental and physical component summary scale (MCS/PCS) of the HRQOL questionnaire (12-Item Short Form Health Survey V.2) and the single item SRH. To estimate educational health inequalities, we calculated the regression-based Slope Index of Inequality (SII) and Relative Index of Inequality (RII). Time trends in inequalities were assessed by the inclusion of a two-way interaction term between school education and time. Results: With increasing age, educational inequalities in PCS and poor SRH decreased whereas they rose in MCS. Over time, health inequalities decreased in men aged 65–79 years (MCSSII =2.76, 95% CI 0.41 to 5.11; MCSRII =1.05, 95% CI 1.01 to 1.10; PCSSII =2.12, 95% CI −0.27to 4.51; PCSRII =1.05, 95% CI 1.00 to 1.11; poor SRHSII =−0.10, 95% CI −0.19 to 0.01; poor SRHRII =0.73, 95% CI 0.48 to 1.13) and among women of that age for MCS (MCSSII =2.82, 95% CI 0.16 to 5.50; MCSRII =1.06, 95% CI 1.01 to 1.12). In contrast, health inequalities widened in the 'later working life' among women (PCSSII =−2.98, 95% CI −4.86 to −1.11; PCSRII =0.94, 95% CI 0.90 to 0.98; poor SRHSII =0.07, 95% CI 0.00 to 0.14) while remained largely stable at old age for both genders. Conclusions: We found distinctive patterns of health inequality trends depending on gender and life stage. Our findings suggest to adopt a differentiated view on health inequality trends and to pursue research that explores their underlying determinants.